Broadband maps of eROSITA and their comparison with the ROSAT survey - Zheng, Xueying; Ponti, Gabriele; Freyberg, Michael; Sanders, Jeremy; Locatelli, Nicola; Merloni, Andrea; Strong, Andy; Sasaki, Manami; Comparat, Johan; Becker, Werner; Kerp, Juergen; Maitra, Chandreyee; et al. (Astronomy & Astrophysics, 2024)
By June of 2020, the extended ROentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spectrum Roentgen Gamma observatory had completed its first of the planned eight X-ray all-sky survey (eRASS1). The large effective area of the X-ray telescope makes it ideal for a survey of the faint X-ray diffuse emission over half of the sky with an unprecedented energy resolution and position accuracy. In this work, we produce the X-ray diffuse emission maps of the eRASS1 data with a current calibration, covering the energy range from 0.2 to 8.0 keV. We validated these maps by comparison with X-ray background maps derived from the ROSAT All Sky Survey (RASS). We generated X-ray images with a pixel area of 9 arcmin2 using the observations available to the German eROSITA consortium. The contribution of the particle background to the photons was subtracted from the final maps. We also subtracted all the point sources above a flux threshold dependent on the goal of the subtraction, exploiting the eRASS1 catalog that will soon be available. The accuracy of the eRASS1 maps is shown by a flux match to the RASS X-ray maps, obtained by converting the eROSITA rates into equivalent ROSAT count rates in the standard ROSAT energy bands R4–R7, within 1.25σ. We find small residual deviations in the R4–R6 bands, where eROSITA tends to observe lower flux than ROSAT (∼11%), while a better agreement is achieved in the R7 band (∼1%). The eRASS maps exhibit lower noise levels than RASS maps at the same resolution above 0.3 keV. We report the average surface brightness and total flux of different large sky regions as a reference. The detection of faint emission from diffuse hot gas in the Milky Way is corroborated by the consistency of the eRASS1 and RASS maps shown in this paper and by their comparable flux dynamic range.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Galaxy: halo; plasmas; techniques: image processing; X-rays: diffuse background; X-rays: ISM